Neutrophil-derived microvesicles enter cartilage and protect the joint in inflammatory arthritis - Headland, Sarah E.; Jones, Hefin R.; Norling, Lucy V.; Kim, Andrew; Souza, Patricia R.; Corsiero, Elisa; Gil, Cristiane D. [UNESP]; Nerviani, Alessandra; Dell'accio, Francesco; Pitzalis, Costantino; Oliani, Sonia M. [UNESP]; Jan, Lily Y.; et al. (American Association for the Advancement of Science (AAAS), 2015)
Microvesicles (MVs) are emerging as a new mechanism of intercellular communication by transferring cellular lipid and protein components to target cells, yet their function in disease is only now being explored. We found that neutrophilderived MVs were increased in concentration in synovial fluid from rheumatoid arthritis patients compared to paired plasma. Synovial MVs overexpressed the proresolving, anti-inflammatory protein annexin A1 (AnxA1). Mice deficient in TMEM16F, a lipid scramblase required for microvesiculation, exhibited exacerbated cartilage damage when subjected to inflammatory arthritis. To determine the function of MVs in inflammatory arthritis, toward the possibility of MV-based therapeutics, we examined the role of immune cell-derived MVs in rodent models and in human primary chondrocytes. In vitro, exogenous neutrophil-derived AnxA1+ MVs activated anabolic gene expression in chondrocytes, leading to extracellular matrix accumulation and cartilage protection through the reduction in stress-adaptive homeostatic mediators interleukin-8 and prostaglandin E2. In vivo, intra-articular injection of AnxA1+ MV lessened cartilage degradation caused by inflammatory arthritis. Arthritic mice receiving adoptive transfer of whole neutrophils displayed abundant MVs within cartilage matrix and revealed that MVs, but not neutrophils themselves, can penetrate cartilage. Mechanistic studies support a model whereby MV-associated AnxA1 interacts with its receptor FPR2 (formyl peptide receptor 2)/ALX, increasing transforming growth factor-p production by chondrocytes, ultimately leading to cartilage protection. We envisage that MVs, either directly or loaded with therapeutics, can be harnessed as a unique therapeutic strategy for protection in diseases associated with cartilage degeneration.